Roadmap Karya Ilmiah Mahasiswa Fakultas Teknik dengan Menggunakan Analisis Bibliometrik - Susiani Susiani; Tessa Simahate; Beatrix Br. Nainggolan; Siti Nurbaidah; Cut Lidya Mutia; Muhammad Khomaini Wahyudi (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
The purpose of this research is to determine the results of the theses by students at the Faculty of Engineering from 2017 to 2021 and their suitability which includes: (1) the field of science that is being examined, (2) boring topics that are no longer in demand, and (3) Trends in the distribution of topics growing based on the Dewey Decimal Classification (DDC) standard. This is a quantitative and qualitative research carried out to determine the distribution of thesis topics as the basis for developing the roadmap of each study program at the Faculty of Engineering, the State University of Medan. Data were collected from the repository and tabulated data tabulations of the summary of results. The results indicate that the number of undergraduate thesis at the Faculty of Engineering, the State University of Medan from 2017 to 2021 is 1,987 titles. The mapping of fields of science based on DDC showed the topics of each study program in the Faculty of Engineering. Based on the data, the in-demand topics for each study program are Construction of Buildings; Care of hair, face, skin, nails; Electronics; Motor Land Vehicles, Cycles (Automotive Engineering); Technical Drawing; Cooking; Pattern Design and Patternmaking; Handicrafts Structural Engineering and Underground Construction; Cutting, Disassembling, Sawing Tools.